Desire, Death and Characterisation in Henry James’ Daisy Miller - Nuru, Aminu Ahmed; Nuru, Ahmed; Abubakar, Abdulkadir; Yerimah, Christiana David (STAIN Majene, 2024)
The paper offers a close textual analysis of Henry James’ classic novella, Daisy Miller. The analysis explores the conflict of desire the female protagonist is exposed to in the society, and how the woman’s desire is linked with death. James’ Daisy Miller depicts the struggle of a woman to articulate and demonstrate her experience of ideal lifestyle in a foreign environment. In this realist fiction, the female protagonist is seen in constant conflict with both the men and women surrounding her as she sticks to the path she feels is ideal for her. She finds herself battling with a new culture different from her own. At the end, the research concludes that Daisy’s death in the novel is an attempt by the author to achieve a “pure” work of art. His motive is clear: he does not intend to deviate from what his society considers pure literature. His attitudes on gender and sexuality seem largely to conform to the accepted social structures of his time.